Extraordinarily large permittivity modulation in zinc oxide for dynamic nanophotonics. (March 2021) - Saha, Soham; Dutta, Aveek; DeVault, Clayton; Diroll, Benjamin T.; Schaller, Richard D.; Kudyshev, Zhaxylyk; Xu, Xiaohui; Kildishev, Alexander; Shalaev, Vladimir M.; Boltasseva, Alexandra
Graphical abstract: Abstract: The dielectric permittivity of a material encapsulates the essential physics of light-matter interaction into the material's local response to optical excitation. Photo-induced modulation of the permittivity can enable an unprecedented level of control over the phase, amplitude, and polarization of light. Therefore, the detailed dynamic characterization of technology-relevant materials with substantially tunable optical properties and fast response times is a crucial step to realize tunable optical devices. This work reports on the extraordinarily large permittivity changes in zinc oxide thin films (up to −3.6 relative change in the real part of the dielectric permittivity at 1600 nm wavelength) induced by optically generated free carriers. We demonstrate broadband reflectance modulation up to 70% in metal-backed oxide mirrors at the telecommunication wavelengths, with picosecond-scale relaxation times. The epsilon near zero points of the films can be dynamically shifted from 8.5 µm to 1.6 µm by controlling the pump fluence. The modulation can be selectively enhanced at specific wavelengths employing metal-backed zinc oxide disks while maintaining picosecond-scale switching times. This work provides insights into the free-carrier assisted permittivity modulation in zinc oxide and could enable the realization of novel dynamic devices for beam-steering, polarizers, and spatial light modulators.